Effects of Cholecalciferol on Key Components of Vitamin D-Endo/Para/Autocrine System in Experimental Type 1 Diabetes - Anna Mazanova; Ihor Shymanskyi; Olha Lisakovska; Lala Hajiyeva; Yulia Komisarenko; Mykola Veliky (International Journal of Endocrinology)
Objectives. Recent prospective studies have found the associations between type 1 diabetes (T1D) and vitamin D deficiency. We investigated the role of vitamin D in the regulation of 25OHD-1α-hydroxylase (CYP27B1) and VDR expression in different tissues of T1D rats. Design. T1D was induced in male Wistar rats by streptozotocin (55 mg/k b.w.). After 2 weeks of T1D, the animals were treated orally with or without vitamin D3 (cholecalciferol; 100 IU/rat, 30 days). Methods. Serum 25-hydroxyvitamin D (25OHD) was detected by ELISA. CYP27A1, CYP2R1, CYP27B1, and VDR were assayed by RT-qPCR and Western blotting or visualized by immunofluorescence staining. Results. We demonstrated that T1D led to a decrease in blood 25OHD, which is probably due to the established downregulation of CYP27A1 and CYP2R1 expression. Vitamin D deficiency was accompanied by elevated synthesis of renal CYP27B1 and VDR. Conversely, CYP27B1 and VDR expression decreased in the liver, bone tissue, and bone marrow. Cholecalciferol administration countered the impairments of the vitamin D-endo/para/autocrine system in the kidneys and extrarenal tissues of diabetic rats. Conclusions. T1D-induced vitamin D deficiency is associated with impairments of renal and extrarenal CYP27B1 and VDR expression. Cholecalciferol can be effective in the amelioration of diabetes-associated abnormalities in the vitamin D-endo/para/autocrine system.